2016
DOI: 10.1371/journal.pone.0157747
|View full text |Cite
|
Sign up to set email alerts
|

A Flavonoid Compound Promotes Neuronal Differentiation of Embryonic Stem Cells via PPAR-β Modulating Mitochondrial Energy Metabolism

Abstract: Relatively little is known regarding mitochondrial metabolism in neuronal differentiation of embryonic stem (ES) cells. By using a small molecule, present research has investigated the pattern of cellular energy metabolism in neural progenitor cells derived from mouse ES cells. Flavonoid compound 4a faithfully facilitated ES cells to differentiate into neurons morphologically and functionally. The expression and localization of peroxisome proliferator-activated receptors (PPARs) were examined in neural progeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
(67 reference statements)
1
8
0
Order By: Relevance
“…However, in-depth studies are needed to fully understand how flavone derivatives regulate astrocyte function and promote astrocytogenesis especially in NSC by PD98059, compound 2, and 3. Like our results, flavonoids have been known to regulate NSC fate [47,48]. It has been known that epigallocatechin-3-gallate induces proliferation and promotes neurogenesis of mouse cochlear NSCs [47].…”
Section: The 3 -Methoxy Group (Methoxy Group At R 2 Position) and Nonsupporting
confidence: 86%
“…However, in-depth studies are needed to fully understand how flavone derivatives regulate astrocyte function and promote astrocytogenesis especially in NSC by PD98059, compound 2, and 3. Like our results, flavonoids have been known to regulate NSC fate [47,48]. It has been known that epigallocatechin-3-gallate induces proliferation and promotes neurogenesis of mouse cochlear NSCs [47].…”
Section: The 3 -Methoxy Group (Methoxy Group At R 2 Position) and Nonsupporting
confidence: 86%
“…Several kinds of flavonoids are known to regulate cell adhesion, proliferation, and differentiation in stem cells [42][43][44]. To determine the role of flavonoid of PBMC-hiPSCs, we added one of the flavonoids with differential structures during the culturing process of the hiPSCs (Supplementary Figure S2).…”
Section: 2 -Dhf Treatment Promoted Proliferation and Suppressed Dissociation-induced Apoptosis Of Hipscsmentioning
confidence: 99%
“…For example, PPARβ/δ controls on a transcriptional level the endothelial differentiation gene (Edg)-2 and PPARβ/δ agonist stimulation enhances the vasculogenic potential of endothelial progenitor cells (EPCs) [ 110 ]. Moreover, it has been shown that PPARβ/δ can promote osteoblast differentiation via Wnt signaling [ 30 ], in a keratinocyte fatty acid binding protein (K-FABP)-dependent manner keratinocyte differentiation [ 111 ], early adipocyte differentiation via PPARγ [ 112 , 113 ], late sebocyte differentiation [ 114 ], oligodendrocyte [ 115 , 116 ] and neural [ 117 ] differentiation, as well as p53- and SOX2-mediated differentiation of neuroblastoma cells [ 118 ]. Finally, the PPARβ/δ target gene FoxO1 plays an important role as negative regulator of skeletal muscle differentiation [ 119 , 120 ].…”
Section: Pparβ/δ Controls Basic Mechanisms Of Wound Healing and Rementioning
confidence: 99%